2003
DOI: 10.1023/a:1026029000085
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Several activators of soluble guanylate cyclase were investigated as potential inhibitors of rat liver mitochondrial monoamine oxidases (MAO) A and B. They all fitted into the previously designed "molds" of substrate-inhibitor binding sites of these enzymes. However, only two of them, NO donors (7-nitro-benzotetrazine-1,3-dioxide (7-NBTDO) and benzodifuroxan), caused nonselective inhibition of MAO A and MAO B with IC(50) values of 1.3-1.6 and 6.8-6.3 microM, respectively. The inhibitory effect on both MAO A an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 11 publications
0
12
0
1
Order By: Relevance
“…The endogenous dipeptide L-carnosine (β-alanyl-L-histidine) [1][2][3] is found in different body organs such as the stomach, kidney and at elevated levels in skeletal and cardiac muscles as well as in brain tissue in olfactory bulb and hippocampus. [4,5] Owing to its water solubility, carnosine levels are found to be particularly elevated in cytosolic cellular fractions.…”
Section: Introductionmentioning
confidence: 99%
“…The endogenous dipeptide L-carnosine (β-alanyl-L-histidine) [1][2][3] is found in different body organs such as the stomach, kidney and at elevated levels in skeletal and cardiac muscles as well as in brain tissue in olfactory bulb and hippocampus. [4,5] Owing to its water solubility, carnosine levels are found to be particularly elevated in cytosolic cellular fractions.…”
Section: Introductionmentioning
confidence: 99%
“…[24] The endogenous dipeptide L-carnosine (β-alanyl-L-histidine) was discovered by Gulewitsch and Amiradzibi [25] from muscle tissue extracts in 1900 [26,27] and is found in several organs including the brain (olfactory bulb and hippocampus) [28], cardiac muscle, kidney and stomach. [29,30] In the skeletal muscle and nerve cells it is found at concentrations of up to 20 mM.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also demonstrated that Bfx derivatives interact with the thiol groups (À SH) present in the cysteine residues, often leading to enzymatic inhibition. [61,62] Therefore, we hypothesized that the Bfx nucleus could lead to the formation of a nitrous intermediate after biotransformation, which then served as an electrophilic site that would lead to the formation of an adduct after interaction with the cysteine residues (À SH) acting as nucleophiles.…”
Section: Initial In Vitro Biological Studiesmentioning
confidence: 99%